Once when I was scared - Pittman, Helena Clare; Rand, Ted (New York : Dutton, 1988)
Grandfather tells how, when he was a child, he coped with fear during a journey alone through a dark wood to get hot coals to heat the family cabin.
School Library Journal starred.
Booklist.
Horn Book.
3.3
K-3
Keywords: Fear -- Fiction; Fear -- Fiction; Fear -- Fiction